2012
DOI: 10.1590/s0100-204x2012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Épocas de semeadura e desempenho agronômico de cultivares de soja

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de épocas de semeadura no desempenho agronômico de cultivares de soja em São Domingos, SC, e indicar as cultivares mais estáveis e adaptadas a cada época. O experimento foi conduzido durante dois anos agrícolas (2008/2009 e 2009/2010), com seis cultivares e quatro épocas de semeadura (15/10, 15/11, 15/12 e 15/1), em delineamento experimental de blocos ao acaso, com três repetições e parcelas com área útil de 3,6 m². A metodologia AMMI (modelos de efeitos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
1
42

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 23 publications
11
58
1
42
Order By: Relevance
“…The photoperiod duration has been related to the length of reproductive development and to the growth rate of soybean (Glycine max) (Kantolic & Slafer, 2007), which is a short day crop as well as chia. Meotti et al (2012) and Jiang et al (2011) reported a decrease in individual mass of seeds with the delay of the sowing date in soybean disagreeing with our results. The mass of one thousand seeds in this work are close to those obtained by Ixtaína et al (2008), which reported a mass of one thousand chia seeds of 1.323 g in a study in Argentina.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The photoperiod duration has been related to the length of reproductive development and to the growth rate of soybean (Glycine max) (Kantolic & Slafer, 2007), which is a short day crop as well as chia. Meotti et al (2012) and Jiang et al (2011) reported a decrease in individual mass of seeds with the delay of the sowing date in soybean disagreeing with our results. The mass of one thousand seeds in this work are close to those obtained by Ixtaína et al (2008), which reported a mass of one thousand chia seeds of 1.323 g in a study in Argentina.…”
Section: Resultscontrasting
confidence: 99%
“…Plants sown in at this time were rapidly induced to flowering, had a lower yield in branches and, consequently, a lower number of ears per plant, which contributed to the lower seed yield. This response is typical of a short day plants which, when sown in late dates, are affected by the decrease of the crop cycle in response to the smaller photoperiod, thus reducing the time to produce and translocate photo-assimilates to grains (Jiang et al, 2011;Meotti et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Essa tendência pode ser observada reiteradas vezes em outras pesquisas, o que justifica estudos que identifiquem fatores ambientais específicos envolvidos na manifestação desse tipo de interação. Só assim se poderá mitigar os efeitos indesejáveis dos ambientes e explorar seus efeitos positivos de modo mais eficiente (Yan, 2001;Oliveira et al, 2006;Asfaw et al, 2009;Martins et al, 2012;Meotti et al, 2012 …”
Section: Tabela 4 Autovalores (L Kunclassified
“…Para a soja, em razão das diferenças edafoclimáticas dos ambientes de cultivo e da contínua liberação de cultivares, são necessários estudos regionalizados para que se possa avaliar melhor o efeito da interação genótipo x ambiente (GxE), nas diferentes épocas de semeadura. A espécie é bastante sensível à variação do ambiente (Meotti et al, 2012).…”
Section: Introductionunclassified
See 1 more Smart Citation